Enhancing TIG Welding Parameters For Direct Tensile Load (DT-load) On Various Steel Thicknesses - Amar, Amar; Sukarman, Sukarman; Khoirudin, Khoirudin; Mulyadi, Dodi; Basit, Arul; Suhara, Ade; Shieddieque, Apang Djafar; Cahyo, Tegar Dwi (Jurnal Polimesin, 2024)
The car body repair process is integral to vehicle development and structural repair. The primary objective of this study is to enhance the quality of thin material welding utilized in automobile body repair. The impetus for this research stems from the necessity to improve the structural integrity and longevity of thin materials prone to deformation throughout the welding procedure while minimizing distortion. This study aims to identify optimal parameters for the tungsten inert gas welding (TIG welding) process on thin materials, particularly for automobile body rearrangement. The Taguchi method conducted the experimental analysis of variations in welding parameters, including electrode diameter, gas flow rate, and welding current. Adjusting TIG welding parameters to their optimal values significantly improves weld joint direct tensile load (DT-load) and overall structural quality, according to the findings of this study. ANOVA analysis and the S-N ratio indicate that gas flow rate and welding current are significant determinants of the quality of welded joints in thin materials. This research contributes to a better understanding of the optimal parameters for fusing thin materials, particularly in automobile body repair. The automotive industry can use these findings as a guide to enhance the quality and strength of welding processes, which are critical to the structural integrity of vehicles.